Application of Media Level Up Pop-Up Book in Improving the Initial Reading Ability of Grade 1 Elementary School Students - Wahdini Rohmah Jaelani; Dede Margo Irianto (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This study discusses the application of level-up pop-up book media in improving the beginning reading skills of 1st grade students. The research approach used is a qualitative approach with the case study method. In this study, researchers conducted observations, interviews, and analyzed documents. The result of this research is that the application of level up pop media. This up book can help improve the target students’ initial reading skills. However, it is necessary to pay attention to several aspects in the application of this media in order to get maximum results.